Synthesis, Characterization, and Antimicrobial Potential of Some Chlorinated Benzofuran Chalcones - Coskun, Demet; Dalkilic, Semite; Dalkilic, Lutfiye Kadioglu; Coskun, Mehmet Fatih (Mattioli 1885, 2021)
Study Objectives: The reaction of 5-chlorosaliciylaldehyde with chloroacetone and potassium -carbonate was used to prepare 1-(5-chloro-1-benzofuran-2-yl) ethanone (1) for starting reagent purposes. A new series of 1-(5-chloro-1-benzofuran-2-yl) ethanone-substituted chalcones 3a-i was synthesized using different substituted aromatic aldehydes in basic conditions by the Claisen-Schmidt condensation reaction. Materials and Methods: Structural analysis of the synthesized compounds was characterized by FT-IR and H-1-C-13-NMR spectroscopy techniques. The antimicrobial properties of the chalcone derivatives (3a-i) were evaluated against the bacterial strains Escherichia coli ATCC 25322, Klebsiella pneumoniae ATCC70060, -Bacillus megaterium, Staphylococcus aureus using the Agar well method. Results: New synthesized compounds demonstrated significant level antimicrobial activity against all bacteria. Conclusion: We described the synthesis of a new series of chloro-benzofuran chalcone hybrids as possible antibacterial agents in this paper.
Keywords: Benzofuran; chalcone; antimicrobial effects; MBC; MIC; Chloro-benzofuran chalcone hybrids